Cyclic shear behaviour of steel box girders experiment and analysis. - Chusilp, Praween (Earthquake engineering & structural dynamics.)
An experimental investigation of the cyclic shear behaviour of steel box girders was conducted on one quarter scale models, comprising of two specimens with longitudinally unstiffened webs and one speciment with longitudinally stiffened webs. All the specimens exhibited ductile behaviour. The tests evidenced significant increases in the shear strength and energy dissipation capacity regarding the use of thicker webs and the provision of longitudinal web stiffeners. The web stiffeners also enhanced the stable hysteresis behaviour without substantial degradation in the energy dissipation due to pinching. The test results are compared with the shear behaviour simulated by inelastic large deformation analysis incorporated with a sophisticated constitutive model. The hysteresis behaviour, peak cyclic shear stresses, energy dissipation, and deformation shapes of the three specimens are satisfactorily predicted by the analysis. It is verified that the presented analytical method can be used precisely for further investigations of box girders in shear.